#TITLE_ALTERNATIVE# - HARIS SETIAWAN (NIM: 251 10 302); Pembimbing: Dr. Ir. Kosasih Prijatna, M.Sc., RANUH
This Thesis aims to investigate the characteristics of Halmahera Eddy and Mindanao Eddy. The final results are expected from this Thesis is obtaining Eddies characteristic table that contains information about the dynamics of the Eddies phenomenon. The research area covers the western Pacific Ocean region that is geographically located at coordinates 10º to -3º latitude and 125º to 140º longitude . The data used in this study which is the Sea Level Anomaly (SLA) from satellite altimetry missions Topex/Poseidon and ERS-2 were obtained from the Radar Altimeter Database System (RADS), with the observation period from January 1996 to December 1998. Sea surface topography obtained after interpolation using Spatio-Temporal Wighted method. The sea surface geostrophic currents can be calculated based on water level differences.From the results obtained show that the phenomenon of Eddies in the western Pacific Ocean region already can be detected from the flow velocity vectors generated from the sea surface topography through the interpolation of the altimetry satellite data. Eddies phenomenon is more often detected when normal conditions compared to conditions of El Niño or La Niña.